Seasonal variance in the incidence rate of epistaxis - Ahsanuzzaman Khan, M.; Wahab, M. Abdul; Alam, M. Monsur; Tabassum, Taniza (International Journal of Research in Medical Sciences, 2023)
Background: Epistaxis, commonly known as a nosebleed, is a medical term that refers to the occurrence of bleeding from the nose. This study aimed to assess the seasonal variance in the incidence rate of epistaxis. Methods: This was a cross-sectional observational study that was conducted in the department of otolaryngology and head-neck surgery (ENT) at Combined Military hospital (CMH), Chattogram from January 2013 to December 2016 and in CMH, Dhaka from January 2017 to July 2019. In total 165 patients who reported complaints of nose bleeding to the ENT Outpatient Department or Emergency unit of the aforementioned hospitals were enrolled in this study as the study subjects. All the patients were diagnosed based on, clinical examination, history, and radiological and laboratory investigations. All data were processed, analyzed and disseminated by using MS office. Results: The mean age of the participants was 34.44 years; the majority (21.8%) were from the age group of 11-20 years. Bilateral nasal bleeding was in 108 (65.5%) cases, 125 (75.8%) patients had the first episode of bleeding and 117 (70.9%) patients had anterior epistaxis. In analyzing the monthly wise incidences rate of epistaxis among participants we observed that, in February (11%), March (10%), June (10%), July (13%) and December (15%) the incidence rates were higher than in other months. In evaluating the seasonal variation of epistaxis among our participants we observed that the highest incidences occurred in the winter season which was 32% followed by 30% in the summer season. Conclusions: Younger male individuals are mainly prone to epistaxis. The frequency of the incidence of epistaxis during the winter and summer seasons is higher than in other seasons.